A 'wiring diagram' for sink strength traits impacting wheat yield potential. (5th November 2022) - Slafer, Gustavo A; Foulkes, M John; Reynolds, Matthew P; Murchie, Erik H; Carmo-Silva, Elizabete; Flavell, Richard; Gwyn, Jeff; Sawkins, Mark; Griffiths, Simon
Abstract: Identifying traits for improving sink strength is a bottleneck to increasing wheat yield. The interacting processes determining sink strength and yield potential are reviewed and visualized in a set of 'wiring diagrams', covering critical phases of development (and summarizing known underlying genetics). Using this framework, we reviewed and assembled the main traits determining sink strength and identified research gaps and potential hypotheses to be tested for achieving gains in sink strength. In pre-anthesis, grain number could be increased through: (i) enhanced spike growth associated with optimized floret development and/or a reduction in specific stem–internode lengths and (ii) improved fruiting efficiency through an accelerated rate of floret development, improved partitioning between spikes, or optimized spike cytokinin levels. In post-anthesis, grain, sink strength could be augmented through manipulation of grain size potential via ovary size and/or endosperm cell division and expansion. Prospects for improving spike vascular architecture to support all rapidly growing florets, enabling the improved flow of assimilate, are also discussed. Finally, we considered the prospects for enhancing grain weight realization in relation to genetic variation in stay-green traits as well as stem carbohydrate remobilization. The wiring diagrams provide a potential workspace for breeders and crop scientists to achieve yield gains in wheat and other field crops. Abstract : Using a set of 'wiring diagrams' in critical pre- and post-anthesis periods, we reviewed traits determining wheat sink strength, relevant for further improving yield potential, identifying research gaps to be studied.